Preoperative management and anticoagulant efficacy in atrial myxoma-associated acute ischemic stroke: a case report and literature review - Chen, Yu; Huang, Qian; Bai, Chengping; Zhang, Hao; Zhang, Bo (Frontiers in Cardiovascular Medicine, 2024)
Acute ischemic stroke (AIS) is a common complication of atrial myxoma (AM), and most emboli originate from a thrombus attached to the surface of the myxoma, with occasional shedding of tumor fragments leading to stroke. Clinical manifestations of AM include mitral valve obstruction, systemic embolism, and weakness. However, neurological deficits and other nonspecific manifestations may mask the presence of AM. The surgical resection is the most effective treatment for these conditions. However, the main problem is the lack of consensus regarding the prevention and treatment of stroke complicated by myxoma during the perioperative period. This study aims to improve the diagnosis and treatment of AM and the associated AIS. Here, we report the case of a 27-year-old patient with AM who presented with chest pain, palpitations, and sudden dizziness and had a stroke under anticoagulant treatment during the admission period. We also reviewed and summarized the clinical presentations and characteristics of similar previously reported cases. Our review emphasized the importance of early diagnosis and appropriate perioperative management of AM and its associated AIS.